Using of acoustic models in mechanical diagnostics - Ploj Virtič, Mateja (Strojniški vestnik, 2008)
This paper presents an acoustical model for control and diagnostics of single stage gear wheels. The model is based on various methods and procedures that as a result provide information about the generatorćs condition, the gear in particular. The acoustical model is part of a complex system that units' different models to meet diagnostics of single stage gear wheels as precise as possible. Using the adaptive FIR filter, acoustical model enables the calculation of impulse response for different notch lengths between 0 and ac. The acoustical model consists of digital FIR filter, modified by LMS algorithm, used to calculate impulse responses in non-linear systems, the model for the calculation of any impulse response and the frequency analysis with the use of FFT for the simulation of frequency spectrums. Frequency spectrum of the simulated sound signal enables an analysis of the error that can be used for calculating the remaining service life and/or determining the control cycle of maintenance.
Keywords: zobniška gonila; preizkušanje; akustično modeliranje; FIR filtri